Potential Role of Lisinopril in Reducing Atherosclerotic Risk: Evidence of an Antioxidant Effect in Human Cardiomyocytes Cell Line - Scisciola, Lucia; Fontanella, Rosaria Anna; Surina; Garofalo, Giovanna; Rizzo, Maria Rosaria; Paolisso, Giuseppe; Barbieri, Michelangela (Frontiers in Pharmacology, 2022)
The cellular mechanisms involved in myocardial ischemia/reperfusion injury (I/R) pathogenesis are complex but attributable to reactive oxygen species (ROS) production. ROS produced by coronary endothelial cells, blood cells (e.g., leukocytes and platelets), and cardiac myocytes have the potential to damage vascular cells directly and cardiac myocytes, initiating mechanisms that induce apoptosis, inflammation, necrosis, and fibrosis of myocardial cells. In addition to reducing blood pressure, lisinopril, a new non-sulfhydryl angiotensin-converting enzyme (ACE) inhibitor, increases the antioxidant defense in animals and humans. Recently, it has been shown that lisinopril can attenuate renal oxidative injury in the l-NAME-induced hypertensive rat and cause an impressive improvement in the antioxidant defense system of Wistar rats treated with doxorubicin. The potential effect of lisinopril on oxidative damage and fibrosis in human cardiomyocytes has not been previously investigated. Thus, the present study aims to investigate the effect of different doses of lisinopril on oxidative stress and fibrotic mediators in AC16 human cardiomyocytes, along with a 7-day presence in the culture medium. The results revealed that AC16 human cardiomyocytes exposed to lisinopril treatment significantly showed an upregulation of proteins involved in protecting against oxidative stress, such as catalase, SOD2, and thioredoxin, and a reduction of osteopontin and Galectin-3, critical proteins involved in cardiac fibrosis. Moreover, lisinopril treatment induced an increment in Sirtuin 1 and Sirtuin 6 protein expression. These findings demonstrated that, in AC16 human cardiomyocytes, lisinopril could protect against oxidative stress and fibrosis via the activation of Sirtuin 1 and Sirtuin 6 pathways.